Evaluation of musculoskeletal complaints, treatment approaches, and patient perceptions in family medicine clinics in a tertiary center in Jordan: a cross-sectional study - Moh’d S. Dawod; Mohammad N. Alswerki; Ahmad F. Alelaumi; Jehad Feras AlSamhori; Rana J. Rahhal; Lina Khraisat; Eman Mohammad Arabas; Hussein M. Bdair; Reem M. Alhyari; Mohammad Shahin; Mohammad Abu Hilal; Alaa Y. Akel; et al. (BMC Primary Care)
Abstract Background Musculoskeletal (MSK) conditions, such as back pain and joint disorders, are common globally and significantly burden healthcare systems. Family medicine clinics serve as the first point of care, requiring providers to manage diverse MSK issues and address gender-specific differences, especially in regions with limited resources, like the Middle East. This study evaluates MSK management, gender differences, and patient perceptions in Jordanian family medicine clinics, aiming to improve care strategies and outcomes in similar settings. Methods This cross-sectional study included 500 adults with musculoskeletal complaints at a Jordanian teaching hospital (January–June 2024). Data were collected via interviews and records, focusing on patient perceptions and health profiles. Ethical approval and informed consent were obtained. Analysis was conducted in SPSS with p < 0.05 as the significance threshold. Results In our study of 500 patients (mean age 46.1 years, 61.5% female), key gender differences emerged. Females had a higher prevalence of low back pain (61.9% vs. 38.1%, p = 0.024) and hip pain (100%, p = 0.008), as well as greater anxiety about disease progression (62.2% vs. 37.8%, p = 0.045) and fear of disability (64.2% vs. 35.8%, p = 0.048). Females also reported lower mental health (p = 0.036), sleep quality (p = 0.044), and overall quality of life (p = 0.019). In contrast, males showed higher workload (54.4% vs. 45.6%, p = 0.020), more work-related injuries (82.8%, p < 0.001), and greater disability (p = 0.024) with lower functional status (p = 0.041). These findings underscore significant gender-specific needs in MSK care. Conclusion Our study reveals notable gender-based differences in musculoskeletal complaints and treatment experiences in a Jordanian tertiary setting. Females reported higher rates of low back and hip pain, more frequent referrals, and lower quality of life, while males experienced greater occupational strain, work-related injuries, and disability.